Inter-species comparison of the copepodite stage morphology, vertical distribution, and seasonal population structure of five sympatric mesopelagic aetideid copepods in the western Arctic Ocean - Koguchi, Yunosuke; Tokuhiro, Koki; Ashjian, Carin J.; Campbell, Robert G.; Yamaguchi, Atsushi (Frontiers in Marine Science, 2022)
Aetideidae is a calanoid copepod family dominant in the mesopelagic layer of the Arctic Ocean for which little ecological information is available because species identification, especially of early copepodite stages, is difficult. In this study, we developed a species identification flow for the whole copepodite stages of five sympatric aetideid copepods (Chiridius obtusifrons, Gaetanus tenuispinus, G. brevispinus, Aetideopsis minor, and A. rostrata). Vertical distributions and seasonal population structures of these species were evaluated using a year-round sample time-series collected at the drifting ice station (SHEBA) in the western Arctic Ocean. Combinations of morphological characteristics (prosome length, cephalosome, and prosome widths) were used to identify the early copepodite stages to species. Aetideopsis rostrata was distributed in deep waters (1,032–1,065 m) throughout the year. The other species all were found at 600–700 m during the midnight sun. However, during the polar night, the vertical distributions of each species were distinct, resulting from ascent, descent, or depth maintenance, indicating seasonal vertical migration which may function to reduce inter-specific competition during the polar night when food resources are scarce. Reproduction timing varied among four aetideid copepods: C.obtusifrons and G. tenuispinus showed polar night ascent and reproduction at the end of the polar night, whereas G. brevispinus and A. minor showed descent or depth maintenance during the polar night and reproduction at the beginning of the polar night. There was not sufficient data to examine reproduction timing of A. rostrata. Common for all aetideid species, δ15N values of the adult females indicate more carnivorous feeding modes during the polar night than those in the midnight sun. Such vertical distribution and timing of reproduction variation among these five aetideid copepods may function to reduce species competition in the mesopelagic layer of the Arctic Ocean.